Structural characterization and in vitro osteogenic activity of ABPB-4, a heteropolysaccharide from the rhizome of Achyranthes bidentata. (1st May 2021) - Lin, Zezhou; Li, Tianyu; Yu, Qian; Chen, Haiyun; Zhou, Di; Li, Ning; Yan, Chunyan
Graphical abstract: Highlights: An acidic pectin polysaccharide, ABPB-4, was obtained from Achyranthes bidentata. The structure and surface morphology of ABPB-4 was elucidated for the first time. The proliferation and differentiation effects of ABPB-4 were comparable to those of E2. ABPB-4 showed significant osteogenic activities by upregulating marker genes. ABPB-4 was the first pectin polysaccharide with bone formation activity. Abstract: Achyranthes bidentata is a species of flowering plant that is mainly distributed in China. The A. bidentata rhizome is a famous traditional Chinese medicine that has been widely used to treat lumbago, arthritis, and bone hyperplasia. In this work, A. bidentata rhizome was isolated and purified to obtain a pectic polysaccharide (ABPB-4). Chemical and spectral analyses showed that ABPB-4 had a main chain of →4)- α -d -Gal p A-(1→ and →2, 4)- α -l -Rha p -(1→, and the branch chains included →4)- β -d -Gal p -(1→, →6)- β -d -Gal p -(1→, →3, 6)- β -d -Gal p -(1→, →5)- α -l -Ara f -(1→ and →3, 5)- α -l -Ara f -(1→, and it was terminated with α -l -Ara f -(1→ and β -d -Gal p -(1→. At concentrations of 0.01, 0.02, and 0.04 μmol/L, ABPB-4 significantly promotes the proliferation, differentiation, and mineralization of MC3T3-E1 cells in vitro, and it appreciably enhances the mRNA expression levels of osteogenic-related genes in these cells. Overall, the results reported herein indicate that ABPB-4 has outstanding osteogenic activity, and that it may be used as an anti-osteoporosis agent in the future.